PSYCHOLOGICAL FACTORS OF THE FORMATION OF THE PROCESS OF CHOOSING A PERSON - Matkarimova Mukhabat Abuovna (Journals Park Publishing, 2022)
The article describes the circulation of choice of profession and its relevance, the study of Professional Psychology by foreign and local scientists, the innovations introduced into science. Scientific works of foreign scientists were used effectively in covering the topic of the article. Conclusions from the article can be used in higher educational institutions and vocational schools in the process of preparing young people for the profession.
Keywords: choice of profession, interest, motivation, orientation to the profession